Advanced fixed income analytics - Phoa, Wesley; Shearer, Michael (New Hope, Penn. : Frank J. Fabozzi Associates, 1998)
This book provides an accessible and practical introduction to a number of advanced topics in fixed income theory. It assumes familiarity with the most basic concepts in bond markets- for example, effective duration and convexity, option pricing with the Black-Scholes model, the concept of option-adjusted spread, and mortgage prepayments- together with some practical experience in analyzing bond portfolios.
Includes bibliograpical references and index.
rpm 16/08/16
Loans
Keywords: Fixed-income securities; .Portfolio management; Bond market